A descriptive study of smoking behavior in school-aged children in Indonesia: Analysis of the 2019 Global Youth Tobacco Survey - Ayuningrum, Ika Yuli; Sudaryanto, Wahyu Tri (Paediatrica Indonesiana, 2023)
Background Adolescents face high pressure to participate in smoking behavior. The impact of smoking will not only affect the health of children and adolescents today, but also their later health status in adulthood. Children who start smoking at a young age are at higher risk of nicotine addiction than those who start in adulthood. Over time, this condition leads to continued cigarette consumption with age. Objective To describe smoking behavior in school-aged children in Indonesia. Methods This was a descriptive study using secondary data from The 2019 Global Youth Tobacco Survey (GYTS) in Indonesia. A sample of 7,582 school-aged children (13-15 years) was selected for this study. The study variables were age, sex, spending money, smoking status, age when they first started smoking, number of days of smoking within the last 30 days, average number of cigarettes per day, electric cigarette use, accessibility to electric cigarettes, and information source on electric cigarettes. Results The largest age group in this study was 14 years old (18.21%). Most subjects were female (57.49%). One-third (2,546 children; 33.57%) of the children have tried or experimented with cigarette smoking. Out of those, 722 children (9.52%) started smoking at the age of 12-13 years and 468 children (6.17%) consumed an average of 1 cigarette per day. Two-thirds of the children were already familiar with e-cigarettes (n=6,061 or 79.94%). The e-cigarettes were obtained from other people (8.16%) and information on e-cigarettes were mostly obtained from peers (8.19%). Conclusion a third of school-aged children in Indonesia have tried or experimented with cigarette smoking. Most of the information on cigarette smoking come from their peers.